Karakteristik Fisikokimia dan Sensoris Nugget Kijing (Pilsbryoconcha exilis) - Ina Permata Sari; Herpandi Herpandi; Shanti Dwita Lestari (Jurnal FishtecH, 2018)
The purpose of this research was to observe the effects of threadfin breams surimi (Nemiptarus nematophorus) and mussel (Pilsbryoconcha exilis) to physical, chemical and sensory characteristics of nugget. This research used randomized block design (RBD) consisted of one factor treatment and three replications. Factor treatment consisted of combination ratio threadfin breams surimi and mussel 100% : 0%, 75% : 25%, 50% : 50%, 25% : 75%, 0% : 100%. The variables observed were physical characteristics (elasticity), chemical characteristics (moisture content, ash, protein, fat, carbohydrate, and iron) and sensory analysis on appereance, flavour, taste and texture of the final products. Different combinations of threadfin breams surimi and mussel had significant effect on elasticity (222.53 gf, 278.33 gf, 300.66 gf, 312.13 gf, 452.86 gf), ash content (3.26%, 2.51%, 2.23%, 1.63%, 1.45%), protein content (8.27%, 12.11%, 14.8%, 17.14%, 20.73%), carbohydrate content (17.32%, 14.34%, 11.11%, 8.42%, 3.5%), and iron (23.61%, 18.56%, 12.77%, 7.24%, 1.54%). Based on the results, the greater addition of surimi concentration caused the increasing value of elasticity, protein, and water content. While the greater addition of mussel concentration resulted on the increased value of ash, fat and iron. This research showed that the combination of 75% threadfin breams surimi and 25% mussel produced on nugget with the best characteristics.